Initiation of the breeding season in ewe lambs and goat kids with melatonin implants - Koumas, Alkis; Photiou, C.; Papachristoforou, Christakis (My University, 2007)
Sixty-eight female and 4 male lambs of the Chios breed born in autumn (September–October) and 48 female and 4 male kids of the Damascus breed also born in autumn (November), were used to evaluate the effect of melatonin implants (Regulin®) on the initiation of the breeding season. For each species and sex, half of the animals were either left untreated to serve as controls (C) or received ear implants (females one and males two implants) of melatonin (MEL) in May (spring). Each C and MEL group of females was kept separately and away from males for 5 weeks after implantation and then, C and MEL males were joined with the respective groups for 45 (sheep) and 35 days (goats). Animals not conceiving during the early June–July breeding season, were mated again in September (natural breeding season). The reproductive performance and the 60-day milk yield of animals giving birth during the two seasons were compared. Early in the season (mid November–December), significantly more MEL than C ewes and goats gave birth (75.5% versus 23.5%, p < 0.01; 70.8% versus 37.5%, p < 0.05, respectively). For both species, most of the other characteristics examined were significantly affected by season, but not by treatment. Females giving birth early in the season were approximately 80 days younger at parturition and recorded a lower body weight at mating than those giving birth in the natural February–March season. In the first mating period, the animals mated and conceived had similar body weights to those not mated. The natural, compared with the early June–July mating season, was associated in sheep with higher litter weight at birth (7.0 kg versus 5.8 kg, p < 0.05) and in sheep and goats with a higher number (p < 0.05) of offspring born live (1.78 versus 1.38; 2.0 versus 1.61, respectively) and weaned (1.74 versus 1.36; 1.82 versus 1.35, respectively). Total litter size at birth and 60-day milk yield after weaning, were not significantly different between the two seasons. It could be concluded that melatonin implants administered during the last month of spring in autumn-born female Chios sheep and Damascus goats, advanced the initiation of their breeding season by about 80 days when joined with young males also treated with melatonin implants. The overall reproductive performance and milk yield of animals breeding early, was satisfactory and comparable to that of animals breeding in the natural breeding season.
Keywords: Melatonin; Chios sheep; Damascus goats; Breeding season